Novel Abscisic Acid Antagonists Identified with Chemical Array Screening. Issue 17 (23rd October 2015) - Ito, Takuya; Kondoh, Yasumitsu; Yoshida, Kazuko; Umezawa, Taishi; Shimizu, Takeshi; Shinozaki, Kazuo; Osada, Hiroyuki
Abstract: Abscisic acid (ABA) signaling is involved in multiple processes in plants, such as water stress control and seed dormancy. Major regulators of ABA signaling are the PYR/PYL/RCAR family receptor proteins, group A protein phosphatases 2C (PP2Cs), and subclass III of SNF1‐related protein kinase 2 (SnRK2). Novel ABA agonists and antagonists to modulate the functions of these proteins would not only contribute to clarification of the signaling mechanisms but might also be used to improve crop yields. To obtain small molecules that interact with Arabidopsis ABA receptor PYR1, we screened 24 275 compounds from a chemical library at the RIKEN Natural Products Depository by using a chemical array platform. Subsequent SnRK2 and PP2C assays narrowed down the candidates to two molecules. One antagonized ABA in a competitive manner and inhibited the formation of the PYR1‐ABA‐PP2C ternary complex. These compounds might have potential as bioprobes to analyze ABA signaling. Abstract : Agony for plants : Abscisic acid antagonists RK438 and RK460, with novel chemical structures, were identified from the RIKEN Natural Products Depository. A chemical array screening platform contributed to isolating plant hormone receptor ligands.